A comparative study of National Senior Certificate summative assessments of poetry for four South African official languages at Home Language proficiency. Issue 1 (2nd January 2023) - Moodley, Visvaganthie; Coetser, Adriaan
Abstract: Over the centuries, summative assessment has entrenched itself as a powerful socio-political and educational tool for determining success, or a lack thereof, and is thus critical for shaping a learner's life. This was particularly prevalent during the apartheid era in South Africa when racially differentiated curricula were crafted. This led to severely dysfunctional assessment practices. However, in recognition of the diversity of the nation, with its 11 official languages, and in an attempt to afford all languages equal status, at its inception in 2009, the Department of Basic Education (DBE) established a common language curriculum and guidelines for the high-stakes Grade 12 National Senior Certificate (NSC) examination. This so-called 'equality', however, is scrutinised in this paper, with specific reference to the assessment of poetry, a literary genre that is generally thought to be cognitively demanding. This paper investigates the similarities and dissimilarities in the Grade 12 NSC summative examination practices of four selected dominant languages studied at the Home Language (HL) level of proficiency, i.e., English HL, Afrikaans HL, isiZulu HL and Sesotho HL. Drawing on Moodley's (2018) skills-specific knowledge for validity in the assessment of poetry, Barrett's Taxonomy of Reading Comprehension for cognitive levels, and Umalusi's (Council for Quality Assurance in General and Further Education and Training) criteria for determining the comparability of NSC examination papers, this paper analyses the poetry component of Paper 2 (Literature) from three sets of examinations: October/November 2019, 2020 and 2021. The paper concludes on the degree of comparability and incomparability among the four languages regarding structural and technical presentation; mark allocation and cognitive weighting; cognitive levels and scaffolding of questions; instructional verbs and degree of difficulty; validity; and the washback effect.